Analysis of Teachers' Resources for Integrating the Skills of Creativity and Innovation, Critical Thinking and Problem Solving, Collaboration, and Communication in Science Classrooms - Haryani, E.; Coben, W. W.; Pleasants, B. A-S.; Fetters, M. K. (Jurnal Pendidikan IPA Indonesia, 2021)
The significance of learners acquiring the skills required in the 21st century, including communication skills, teamwork, ICT-related skills and socio-cultural knowledge, imagination, critical thinking, and problem-solving, has been extensively discussed. Integrating the 21st century into the curriculum requires teachers to have knowledge and resources to foster classroom practices. This qualitative study was designed to explore the resources that Indonesian science teachers use in supporting the implementation of the skills of creativity and innovation, critical thinking and problem solving, collaboration, and communication (4Cs) integrated science instruction. Data analyses include surveys, audio recordings of smalls and large group discussions, and group discussion artifacts of 28 Indonesia vocational high school science teachers to identify the type of resources that teachers have had access to support the integration of 4C into science instruction and the extent to which these resources promote the 4C integration into science instruction. The analysis indicates that teachers use multiple resources to help them prepare for 4C integration into teaching practices, including various professional development (PD) programs, various teacher collaborations, curriculum guidelines, and open resources. Teachers found that Teacher Professional Education (TPE) was the most favorable PD program, and curriculum guideline was the least effective for advancing 4C integration. Implications are discussed further.